Vacuum Assisted Closure Therapy versus Standard Wound Therapy for Open Musculoskeletal Injuries - Kushagra Sinha; Vijendra D. Chauhan; Rajesh Maheshwari; Neena Chauhan; Manu Rajan; Atul Agrawal (Advances in Orthopedics)
Background. This study was performed to evaluate the results of vacuum assisted wound therapy in patients with open musculoskeletal injuries. Study Design and Setting. Prospective, randomized, and interventional at tertiary care hospital, from 2011 to 2012. Materials and Methods. 30 patients of open musculoskeletal injuries underwent randomized trial of vacuum assisted closure therapy versus standard wound therapy around the upper limb and lower limb. Mean patient age was years (range, 18 to 76 years). Necrotic tissues were debrided before applying VAC therapy. Dressings were changed every 3 or 4 days. For standard wound therapy, debridement followed by daily dressings was done. Data Management and Statistical Analysis. The results obtained were subjected to statistical analysis. Results. The size of soft tissue defects reduced more than 5 mm to 25 mm after VAC (mean decrease of 26.66%), whereas in standard wound therapy, reduction in wound size was less than 5 mm. A free flap was needed to cover exposed bone and tendon in one case in standard wound therapy group. No major complication occurred that was directly attributable to treatment. Conclusion. Vacuum assisted wound therapy was found to facilitate the rapid formation of healthy granulation tissue on open wounds in the upper limb and lower limb, thus to shorten healing time and minimize secondary soft tissue defect coverage procedures.